Analisis Kesalahan Menyelesaikan Soal Persamaan Garis Lurus pada Siswa Kelas VIII SMP Negeri 2 Wonogiri - Fathimah, Nurul, Prof. Dr. Sutama, M.Pd (2017)
This study aims to find out the mistakes made by students in solving equations straight line. This research is a qualitative research. Data collection techniques used were interviews, observation, and documentation. The results of the analysis indicate the type of errors students, among others: (a) errors language with highest percentage in the problem section gradient is 13.125% (classified as very low), language mistakes are often made students an understanding of mathematical symbols and sentence comprehension questions that granted (b) the misconceptions with highest percentage in the problem section gradient of 15% (classified as very low), the misconceptions that often do students a requirement of two lines perpendicular to each other, arithmetic operations between the numbers of positive and negative, and describes the line equation straight or coordinate point in a graph (c) the error count with the highest percentage in the problem section gradient is 12.5% (classified as very low), counting errors are often made of students is surgery plus, minus, times, and for the numbers positive and negative; and move the segment, so it can be said to be an error in solving equations straight line contained in section gradient and relatively very low.